2016
DOI: 10.5252/z2016n4a2
|View full text |Cite
|
Sign up to set email alerts
|

A catalogue and systematic overview of the shield-tailed snakes (Serpentes: Uropeltidae)

Abstract: We present a catalogue and systematic overview of Uropeltidae Müller, 1832 based on both new and previously published molecular and morphological data, and a new molecular phylogenetic analysis. We support the monophyly and distinctiveness of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 50 publications
2
38
0
Order By: Relevance
“…3). Beddome (1886), Smith (1943) and Pyron et al (2016) report R. sanguineus as having a bright red ventral colour in life, as did Beddome (1863) in his description of the species. However, Wall (1919) reported that this was not true of young specimens of this species, though he did not specify at which size this change occurred.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…3). Beddome (1886), Smith (1943) and Pyron et al (2016) report R. sanguineus as having a bright red ventral colour in life, as did Beddome (1863) in his description of the species. However, Wall (1919) reported that this was not true of young specimens of this species, though he did not specify at which size this change occurred.…”
Section: Discussionmentioning
confidence: 89%
“…Comparative material of Indian Rhinophis is reported in Appendix 1. Taxonomy and taxon spellings follow McDiarmid et al (1999) and Pyron et al (2016). Catalogue numbers of reported specimens bear the following institutional prefixes: BMNH (Natural History Museum, London, UK), BNHS (Bombay Natural History Society, Mumbai, India), BUB (Bangalore University, Bengaluru, India), CAS (California Academy of Sciences, San Francisco, USA), MCZ (Museum of Comparative Zoology, Harvard University, USA), MNHN (Muséum national d'Histoire naturelle, Paris, France), ZMB (Museum fur Naturkunde, Berlin, Germany), ZSI/WGRC (Western Ghats Regional Centre of the Zoological Survey of India, Kozhikode).…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations